2020
DOI: 10.1021/acs.jpclett.0c02445
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Triplets in Single-Photon Double Ionization of Methanol

Abstract: Despite the abundance of data concerning single-photon double ionization of methanol, the spin state of the emitted electron pair has never been determined. Here we present the first evidence that identifies the emitted electron pair spin as overwhelmingly singlet when the dication forms in low-energy configurations. The experimental data show that while the yield of the CH 2 O + + H 3 + Coulomb explosion channel is abundant, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…Few H2+-forming trajectories were found to exhibit long-range inverse harpoon while on an excited state. However, similar to the simulated roaming H 2 dynamics reported by Gope et al ( 50 ), most of the initially excited systems undergo nonadiabatic surface hopping to the ground state before the separation of the neutral H 2 . On the one hand, as can be expected, higher initial excitation exhibits higher KER than trajectories initiated on the ground and first excited state, respectively indicated in Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Few H2+-forming trajectories were found to exhibit long-range inverse harpoon while on an excited state. However, similar to the simulated roaming H 2 dynamics reported by Gope et al ( 50 ), most of the initially excited systems undergo nonadiabatic surface hopping to the ground state before the separation of the neutral H 2 . On the one hand, as can be expected, higher initial excitation exhibits higher KER than trajectories initiated on the ground and first excited state, respectively indicated in Fig.…”
Section: Resultssupporting
confidence: 82%
“…3B show the simulated KER distribution for the CHOH++H2+ channel. More than 200 trajectories are initiated on each of the seven lowest singlet states of the methanol dication, in accordance with the high energy of the EUV photons ( 34 , 50 ). The simulation is terminated once the system is significantly extended after the dissociation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Gope et al. recently confirmed that SPDI predominantly forms the singlet CH 3 OH 2+ states 42 . The fact that theoretical simulations for these systems agree so well with the SPDI experiments allows us to use them to explore questions that cannot be directly resolved by experiments.…”
Section: Introductionmentioning
confidence: 78%
“…In the interstellar medium, trihydrogen is believed to form primarily by the normalH2++normalH2 collisions 3 . Nevertheless, it has been ubiquitously identified as a surprising product of many types of organic molecule ionization processes, including electron impact, 25,26 fast‐ion bombardment, 27,28 multi‐photon double‐ionization (MPDI) by intense laser pulses, 29–37 as well as single photon double‐ionization (SPDI) 38–42 . In particular, H3+ formation from the simplest alcohol (methanol) received special attention due to its abundance in a wide range of interstellar environments 43 …”
Section: Introductionmentioning
confidence: 99%
“…In the next step, the neutral H 2 roams on the PES in the vicinity of the precursor and extracts a proton to form H 3 + . [11][12][13][14][15][16][17] H 2 + , on the other hand, is formed by the long-range electron transfer from the neutral H 2 to the parent dication by a process known as ''inverse harpooning''. 11 The timescale of such intramolecular hydrogen migration has been reported to be B100 fs.…”
mentioning
confidence: 99%